Virtual postgraduate exams and assessments: the challenges of online delivery and optimising performance. Issue 2 (February 2021) - Ellis, R.; Oeppen, R.S.; Brennan, P.A.
Abstract: The COVID-19 pandemic has catalysed the computerisation and online delivery of postgraduate examinations. Social distancing regulations and lockdown measures resulted in many written and clinical examinations being cancelled during the initial surge of the virus. In an effort to reinstate the assessment of trainees and enable career progression, the UK medical regulator, the General Medical Council (GMC) has approved unprecedented changes to clinical examinations, including virtual assessment. We outline the changes made and the advantages and disadvantages of these new examination formats. We discuss ways for candidates and examiners to optimise their virtual environment and develop skills that can improve performance.